Testicular dislocation: Does timing of detection dictate management? A report of two cases - Snehasish Saha; Shamita Chatterjee; Pritin Bera (Annals of Medical Science and Research)
Testicular dislocation is a rare condition after blunt trauma to the pelvis and genitalia. It is often overlooked during initial management after trauma, and patients have been reported to present with the condition after months or years after the trauma. Diagnosis is confirmed by imaging, and management is primarily surgical. However, if patients present early with absence of other injuries requiring surgery, a manual reduction can be attempted to reposition the testis. Early management prevents testicular atrophy and spermatogenic dysfunction. Hence, a physical examination of the groin and genitalia should be mandatory in all patients with high energy trauma to the pelvis and genitalia.